Keefektifan Organisasi dalam Pemberdayaan Sekolah - Busthomi Ibrohim (Universitas Darussalam Gontor, 2009)
In relation with the school, it may be stressed that effectiveness of the school is in its specified procedure to develop a consistent organization based on the need which centralized on the school principal managerial process. Because, the system, management, as well as school procedure and its organizational development lay on the hand of the principal, who is then considered as the evaluation standard. This managerial process can be judged from the function of organizational structure optimally, teachers performance, professional school personnel, the development of learning activity, the implementation of rule and regulation, academic development and the achievement of education aim. Due to this reason, the more skillful is the principal, teacher, and other school personnel the more effective and efficient the whole school system and its management. The main requirement of organizational effectiveness is by understanding various methods how an organization is effective. In this case the manager of an organization is not only to identify various dimensions of critical institutional performance, but to mobile the organization towards effectiveness. The effective school models consist of three levels; school, class, and the student background.